The Relationship Between Life Satisfaction, Parenting Style And Risky Behaviors Among Adolescent: Systematic Review - Abdullah, Norida; Husin, Noraini; Kong, Felicia Hie Lay; Ariffin, Hafzan; Mohammad Rawi, Ali Hafizar (Penerbit Universiti, UTeM, 2017)
Issues related to adolescent risky behaviors are common in Malaysia. There are many factors that resulted to these phenomena. It can be related to the internal and external factors such as adolescent biological changes, parenting style, adolescent’s life satisfaction, the community of the adolescent being brought up, the culture of the society and so on. The adolescent is a development period where they are in between childhood and adulthood, experiencing changes physically, psychologically and also socially. During this period, adolescent spent more time with their friends, and their emotional re activity increased, which also results in the increases of conflicts with parents. The aims of this study are to evaluate the relationship between students’ life satisfaction, parenting style and risky behaviors among the secondary students around Selangor area. The population size for this research is secondary students. There are three questionnaires being administered to the students at two phases. Problem Oriented Screening Instrument for Teenagers (POSIT) will be administered during the first phase while Parenting Style Inventory-II (PSI-II) and Multidimensional Student’s Life Satisfactory Scale (MSLSS) will be administered at the second phase. The present study intends to explore and examine the relationship between life satisfaction, parenting style and risky behaviors among adolescent. This study expected to that the present study results can provide information regarding the parent-adolescent relationship, adolescent life satisfaction during the school day, and the involvement in the risky behavior among adolescent.